Indeks Maslahat sebagai Indikator Alternatif Keberhasilan Pembangunan - Dedi Junaedi (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
The main objective of a country's economic development is an effort to improve the welfare of its people. Various indicators of development success have been offered. Starting from GDP and per capita income, human development index (HDI), people's welfare index (pledge) and economic welfare index (Eurostat). In the perspective of Islam, the various indicators still have weaknesses because they only display worldly statistics, they have not touched the aspect of ukhrawi (afterlife). On that basis, Islam introduced the concept of maqasid al-shariah or benefit as an indicator of the success of development. The benefit to be achieved includes the safeguarding of five basic elements of human life: faith (monotheism), soul, reason, descent, and wealth (wealth). From these five elements we can develop a number of benefit parameters as indicators of complete human development. Keywords: eurostat, ikrar, HDI, benefits, maqasid al-sharia, GDP